SOCIALISATION IN THE FAMILY AND FORMATION OF PRESCHOOL CHILDREN’S CONCEPT OF THE PARENT’S IMAGE - Vikmane, Blāzma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
“Family National Policy Guidelines for 20011-2017 year” underlined that the concept of family is taking shape since birth and will continue in the following years. So the family as primary childs socialization institution has a major role to play in the first picture of the parental pattern formation. It is so important, that the family would facilitate development of concepts of the family model complying with standards in society and would facilitate getting ready for the role of a good father or mother. Children in their games shown as parents educating them: both positive and negative. Unfortunately, as the surveyed preschool teachers mention, quite often children depict their parents as smokers, drunkards and always quarrelling